The Varieties of Ignorance: Imaging of Congenital Variants of Pancreas and Its Ductal System—A Pictorial Review - Sharma, Shaurya; Sureka, Binit; Yadav, Taruna; Panda, Ananya; Khera, Pushpinder Singh (Indian Journal of Radiology and Imaging, 2023)
Congenital variants of the pancreas are being increasingly detected with the widespread use of modern imaging techniques. The underlying embryologic aberration predicts the final appearance of pancreatic development. It is essential to recognize these congenital variants, as many of these have been proven to be associated with pancreatic diseases like recurrent pancreatitis and chronic abdominal pain. Cross-sectional techniques like multidetector computed tomography and magnetic resonance cholangiopancreatography are the most used imaging techniques for the pancreas, where a radiologist comes across these variants. This pictorial aims to classify the type of variant anatomy of the pancreas, their imaging appearances, and their clinical significance.
Keywords: congenital; pancreas; variations; agenesis